Coordination of Village Government in Flood Mitigation in Monas Village, Monano Subdistrict, North Gorontalo Regency - Nurlailah Abdullah; Lisda Van Gobel; Tety Thalib (Institute of Educational, Research, and Community Service, 2023)
The aim of this research is to find out how the village government coordinates in flood management in South Monano Village, Monano District, North Gorontalo Regency. This type of research is descriptive with a qualitative approach method. The research location is Monas Village, Monano District, North Gorontalo Regency. With a research focus, namely planning, communication and direction. The data sources in this research come from primary data obtained from direct informants and secondary data obtained through documents relevant to this research. Data collection uses observation, interviews and documentation methods. Stages of data analysis through data reduction, data presentation and conclusions or verification. The research results show that the planning aspect is not fully optimal, this is because flood management carried out by the village government is limited to making drainage, platduickers, and programs that involve the community. Communication Aspect, that communication regarding flood disaster management in Monas Village has been carried out by the Village Government through socialization, social media and others, but it is still felt to be not optimal and the Direction Aspect, is not yet fully optimal even though guidance has been carried out by the local government in the form of advice on maintenance surrounding environment, cleaning drainage, always standing by in case of rain. The conclusion is that flood disaster management in Monas Village, seen from the aspects of planning, communication and direction, is not yet optimal, which is shown in terms of planning, there is no long-term planning in the form of building embankments along the river which is the main source of flooding, current communication is only limited to providing information to the community in avoiding flooding and the direction given was limited to an appeal not to throw rubbish in the drainage of the waterway. It is recommended that the village government in dealing with floods be expected to have a long-term plan and provide early warnings through the sound of sirens, provide directions for gathering points and always coordinate with the Sar Team so that the village is free from flooding.